A longitudinal Examination of Environmental Reporting Practices in Malaysia - Alrazi, Bakhtiar; Sulaiman, Maliah; Nik Ahmad, Nik Nazli (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
A content analysis of the annual reports of 96 Malaysian companies in 1999, 2003 and 2006 finds that the number of companies reporting on the environment increased from 47 percent in 1999 to 60 percent in 2003, and further increased to 67 percent in 2006. However, the extent of environmental reporting as measured by the number of environmental sentences and disclosure scores (using a self-constructed disclosure index) indicates a low quality of disclosure. Overall, the disclosure is ad-hoc and predisposed towards building a âgood corporate citizenâ image. The increasing trend, however, is consistent with the prediction of social issue life cycle theory.